2018
DOI: 10.15252/emmm.201707918
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DDR 1‐ BCR signalling by nilotinib as a new therapeutic strategy for metastatic colorectal cancer

Abstract: The clinical management of metastatic colorectal cancer (mCRC) faces major challenges. Here, we show that nilotinib, a clinically approved drug for chronic myeloid leukaemia, strongly inhibits human CRC cell invasion in vitro and reduces their metastatic potential in intrasplenic tumour mouse models. Nilotinib acts by inhibiting the kinase activity of DDR1, a receptor tyrosine kinase for collagens, which we identified as a RAS‐independent inducer of CRC metastasis. Using quantitative phosphoproteomics, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 43 publications
(74 reference statements)
5
101
0
Order By: Relevance
“…These results imply that the OSCC cells might have been addicted to overexpressed DDR1 for their survival. In the same vein, targeting DDR1 alone or in combination with other chemotherapies have been suggested in several neoplasms, including metastatic colorectal cancer, K-RAS driven lung adenocarcinoma, and breast carcinoma [14,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that the OSCC cells might have been addicted to overexpressed DDR1 for their survival. In the same vein, targeting DDR1 alone or in combination with other chemotherapies have been suggested in several neoplasms, including metastatic colorectal cancer, K-RAS driven lung adenocarcinoma, and breast carcinoma [14,[52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…In studies of Xie et al (), an association between DDR1 and invasion of gastric cancer cells via EMT has been shown in patients with gastric cancer. Jeitany et al () identified DDR1 as a therapeutic target in colorectal cancer and suggested that inhibition of DDR1 by tyrosine kinase inhibitors could be a useful medical approach in patients with metastatic colorectal cancer. Lu et al () reported that inhibition of DDR1 with a small chemical molecule inhibitor can suppress nasopharyngeal carcinoma cell in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These inhibitors are approved by the FDA and could constitute a new treatment for patients overexpressing DDRs in cancers. For example, recently it has been shown that nilotinib inhibits DDR1 kinase activation and reduces invasion in metastatic colorectal cancer [127]. Dasatinib efficiency has been proven several times.…”
Section: Inhibition Of the Ddrsmentioning
confidence: 99%